1999
DOI: 10.1021/ja9915605
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Electron Transfer in Phytochlorin−[60]Fullerene Dyads

Abstract: Novel molecular electron donor-acceptor (DA) dyads, composed of a phytochlorin donor and a [60]fullerene acceptor, have been photochemically characterized. In these dyads, a pyrrolidine spacer group links the chlorin and the C 60 moieties covalently, forming a rigid dyad with a short and almost constant D-A distance. The photochemical behavior of the metal-free dyads and the corresponding Zn complexes was studied by means of fluorescence and absorption spectroscopies with femto-and picosecond time resolutions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
233
4
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 278 publications
(250 citation statements)
references
References 26 publications
12
233
4
1
Order By: Relevance
“…For dyads 29 and 30, synthesized by Diels Alder and Prato reaction, quenching of the photoinduced chlorine excited states was observed [37,38]. Time-resolved fluorescence and absorption spectroscopy revealed that an intramolecular exciplex was formed upon photoexcitation of the chlorine moiety of 30 [39]. Such an exciplex was not detected for analogous C 60 -porphyrin dyads.…”
Section: -Phytochlorin Dyadsmentioning
confidence: 94%
“…For dyads 29 and 30, synthesized by Diels Alder and Prato reaction, quenching of the photoinduced chlorine excited states was observed [37,38]. Time-resolved fluorescence and absorption spectroscopy revealed that an intramolecular exciplex was formed upon photoexcitation of the chlorine moiety of 30 [39]. Such an exciplex was not detected for analogous C 60 -porphyrin dyads.…”
Section: -Phytochlorin Dyadsmentioning
confidence: 94%
“…The instrumentation and the data analysis procedure have been described earlier. [20,21] 2-(3-Hydroxypropoxy)benzaldehyde: Potassium hydroxide (3.8 g, 56.3 mmol, 85 % purity) was dissolved in EtOH (60 mL). The flask was attached to a reflux condenser with a rubber septum on top and purged with nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…The present decay sequences are qualitatively consistent with those determined for other porphyrin-fullerene dyads. 14,18,38 Conclusion A novel zinc porphyrin-fullerene dyad covalently connected by a disilane bridge (ZnP-Si 2 -C 60 ) was synthesized and fully identified by its 1 H, 13 C, and 29 Si NMR and FAB mass spectra. The quenching paths from 1 ZnP Ã -Si 2 -C 60 are most probably attributed to the charge separation in polar solvents.…”
Section: Resultsmentioning
confidence: 99%